Beyond streets: The role of alleys in Abu Dhabi's and Dubai's network systems - Asim Khanal; Rawan Sohdy Abdelfattah; Khaled Alawadi; Ngoc Hong Nguyen (Journal of Urban Management, 2024)
The network system is defined as the combination of streets and alleys. Although the potential of alleys in complementing street networks is acknowledged, the topic has not received a considerable attention in urban planning practice and scholarship. This paper evaluates alleys’ role in the combined street-alley networks by calculating Information Centrality, a metric in Multiple Centrality Assessment (MCA). The combined network of streets and alleys in thirteen neighborhoods of Abu Dhabi and Dubai have been studied. Findings indicate that alleys may or may not contribute to increment of network efficiency. Generally, the contribution of alleys to efficiency is more significant if the corresponding street network has low efficiency.